A Click Chemistry Approach to Targeted DNA Crosslinking with cis‐Platinum(II)‐Modified Triplex‐Forming Oligonucleotides. (3rd December 2021) - Hennessy, Joseph; McGorman, Bríonna; Molphy, Zara; Farrell, Nicholas P.; Singleton, Daniel; Brown, Tom; Kellett, Andrew
Abstract: Limitations of clinical platinum(II) therapeutics include systemic toxicity and inherent resistance. Modern approaches, therefore, seek new ways to deliver active platinum(II) to discrete nucleic acid targets. In the field of antigene therapy, triplex‐forming oligonucleotides (TFOs) have attracted interest for their ability to specifically recognise extended duplex DNA targets. Here, we report a click chemistry based approach that combines alkyne‐modified TFOs with azide‐bearing cis ‐platinum(II) complexes—based on cisplatin, oxaliplatin, and carboplatin motifs—to generate a library of Pt II ‐TFO hybrids. These constructs can be assembled modularly and enable directed platinum(II) crosslinking to purine nucleobases on the target sequence under the guidance of the TFO. By covalently incorporating modifications of thiazole orange—a known DNA‐intercalating fluorophore—into Pt II ‐TFOs constructs, enhanced target binding and discrimination between target and off‐target sequences was achieved. Abstract : Nucleic acid click chemistry has been used for the development of cis ‐platinum(II)/triplex‐forming oligonucleotide hybrid biomaterials. This modular approach allows the incorporation of cis ‐platinum(II) at practically any location within the probe strand. These hybrid biomaterials display discrete and efficient crosslinking of purine‐rich genetic elements of the GFP gene.